The Appropriateness of Glycerin Enema in Pediatric Patients Visiting the Emergency Department - Min-Jung Kim; Yoo-Jin Choi; Jin-Hee Lee; Hyuksool Kwon; Dongbum Suh (MDPI AG, 2021)
Objectives: We determined whether glycerin enemas were appropriately prescribed in pediatric fecal impaction patients using the Leech score and identified factors that influenced the prescription of glycerin enemas in the pediatric emergency department (PED). Methods: We included patients who received a glycerin enema at the PED of a tertiary teaching hospital. We divided the study subjects into two groups on the basis of their Leech scores: an appropriate enema group (Leech score ≥ 8), and an inappropriate enema group (Leech score < 8). Logistic regression was performed to determine the factors associated with glycerin enema administration. Results: The data of 998 patients, including 446 patients in the inappropriate enema group (Leech score 5.2 ± 1.7) and 552 patients in the appropriate enema group (Leech score 10.1 ± 1.7), were analyzed. A discharge diagnosis of fecal impaction was observed significantly more frequently (57.1%) in the appropriate enema group, and nonspecific abdominal pain (8.3%) and acute gastroenteritis (40.8%) were diagnosed significantly more frequently in the inappropriate enema group (p < 0.05). Constipation (2.8%) and irritability (3.0%) were slightly more common in the appropriate enema group than in the inappropriate enema group (p < 0.05). According to multiple logistic regression, subjects aged 2-8 years (2-4 years, OR 4.24; 4-8 years, OR 2.83), with vomiting (OR 1.72), with irritability (OR 4.52), and with a prolonged last defecation day (OR 1.2) were most likely to receive appropriate enema administration (p < 0.05). Conclusion: The results showed that in those aged 2-8 years, with vomiting and irritability, and with a prolonged last defecation day, an enema was generally administered appropriately.